Variation in Soil Temperature Amid COVID-19 Pandemic Lockdown in Mid Hills of Rajouri and Jammu Districts, J&K, India - Sharma, Rohit; Vikas, Vishaw; Kumar, Deepak; Sharma, Vikas; Mishra, Sunil Kumar (Current Approaches in Science and Technology Research Vol. 1, 2021)
Aim: A preliminary analysis was done to evaluate the impact of lockdown on soil temperature at different depths and comparison with year 2018 and 2019. Methodology and Results: In order to describe the basic features of the data in study, descriptive statistics method was opted. The deviation in soil temperature in Rajouri District from mean value at 5 cm depth observed during lockdown was -8.58% and -4.77% compared to year 2018 and 2019. However the deviation observed from mean value at 10 cm depth was -10.72% and -9.28%. The deviation from mean value at 20 cm depth observed was -2.34% and -1.98%. The average change in soil temperature in Jammu District in morning at 5 cm, 10 cm and 20 cm depth was -3.46%, -3.84% and -7.23% as compared to year 2019 (22nd March to 10th June 2019) mean value and the change in soil temperature in evening at same depths was -7.69%, -6.31% and -4.14% from year 2019 (22nd March to 10th June 2019). The much focus is on Rajouri District as compared to Jammu, so tables and figures are representing Rajouri situation. Conclusion: The study concluded that due to lockdown, there was significant change in soil temperature values at variable depths compared to year 2018 and 2019 in the study region.